Digital Literacy Program Management in Developing the Quality of Graduates - Zaenal Abidin; Abdul Azis; Amirudin Amirudin (Eduprof : Islamic Education Journal, 2026)
Digital literacy is one of the basic literacy that has currently become a necessity in teaching and learning activities, education units must have a strategy to increase digital literacy competency to develop the quality of graduates who are globally competitive. This study aims to examine the digital literacy program at SMP Plus Ulil Albab Cirebon. This research uses a qualitative approach with case study methods and data sources including the Principal, Madrasah Committee, Teachers and Guardians of SMP Plus Ulil Albab Cirebon students. The research instrument is the researcher with data collection based on his methods, namely in depth interviews, observations, and documentation studies and data triangulation. The management of the digital literacy program at SMP Plus Ulil Albab Cirebon is carried out including planning, organizing, implementing and supervision. Planning begins with conducting a SWOT analysis of program needs, then forming the person in charge, program design, satisfaction and effectiveness instrument design, and budget plan.  The organization of the digital literacy program is carried out including the determination and distribution  of job descriptions of the person in charge, and program participants. The implementation of the digital literacy program is carried out in computer laboratory and outdoor spaces, according to the material provided. Supervision is carried out by the principal and school committee periodically once every semester. Based on the results of the study, it is concluded that the management of digital literacy programs in schools contributes to the development of the quality competencies of student graduates at SMP Plus Ulil Albab Cirebon, but there are still several things that need to be improved related to the digital literacy program, including the components of facilities and infrastructure as well as the improvement of human resources and the assessment of program achievement..